Tear Film Pharmacokinetics and Systemic Absorption Following Topical Administration of 1% Prednisolone Acetate Ophthalmic Suspension in Dogs - Sebbag, Lionel; Kirner, Nicolette S.; Wulf, Larry W.; Mochel, Jonathan P. (Frontiers in Veterinary Science, 2020)
The study aimed to determine the tear film pharmacokinetics following topical administration of 1% prednisolone acetate – assessing whether 2 drops would provide a superior kinetic profile compared to 1 drop – and to determine the fraction of an eyedrop that reaches the systemic circulation in dogs. Two separate experiments were conducted in 8 healthy Beagle dogs: (i) Instillation of 1 drop (35 µL) or 2 drops (70 µL) of 1% prednisolone acetate ophthalmic suspension in each eye, followed by tear collections with Schirmer strips from 0 to 720 min; (ii) Instillation of 1 or 2 drops of 1% prednisolone acetate in both eyes 4 times daily for 3 days, followed by blood collection 10-15 min after each topical administration on Day 3. Tear and blood samples were analyzed with high performance liquid chromatography to determine the levels of prodrug (prednisolone acetate), active metabolite (prednisolone) and total prednisolone (prednisolonetotal = prodrug + active metabolite). Prednisolone levels represented 10% and 72% of prednisolonetotal concentrations in tears and plasma, respectively, indicating a greater hydrolysis of prodrug in the blood vs. tear compartment. For eyes receiving 1 or 2 drops, tear film prednisolonetotal concentrations were high ( 3.1 mg/mL) immediately following topical administration but rapidly decreased by 45% at 1 minute and 95% at 15 minutes. No differences were noted between 1 vs. 2 drops in tear film prednisolonetotal concentrations (including maximal concentration, Cmax) or residual drug levels in tears at any time point (P ≥ 0.097); however, instillation of 2 drops provided a higher average tear concentration (Cavg) and overall drug exposure to the ocular surface (AUClast) over the 12-h sampling period (P = 0.009). Average plasma prednisolonetotal concentration represented ≤ 2% of the dose applied to the ocular surface, and did not differ significantly for dogs receiving 1 drop (17 ng/mL) or 2 drops (20 ng/mL) 4 times daily for 3 days (P = 0.438). In sum, topical corticotherapy is beneficial for inflammatory conditions of the canine anterior segment given the relatively high concentrations achieved in tears, although caution is warranted to prevent unwanted local or systemic adverse effects.